PENINGKATAN MANAJEMEN WAKTU BELAJAR SISWA SMA MELALUI INTERVENSI MEDIA PERMAINAN TRADISIONAL ENGKLEK - Denok Lirenda Armadani; Wahyu Widyatmoko (IKIP Siliwangi, 2026)
This study aims to determine the level of student study time management before and after being given group guidance services with simulation games techniques. The simulation games technique is used with the media of the traditional game engklek to create a fun learning atmosphere with cultural elements. This type of research is a pre-experiment with a One-Group Pretest-Posttest design. The population in this study were students of class X-5 SMA Negeri 4 Samarinda, totaling 34 students, with 8 subjects. Sampling using purposive sampling. The results showed that there was an increase in study time management after attending group guidance services with simulation games techniques using the traditional game media engklek. The average pretest result of 89.25 increased to 94.37 on the posttest. The t-test results show that the sig value is 0.002 <0.05 which indicates a difference between the pretest and posttest results.